Antimicrobial Stewardship in a Hematological Malignancy Unit: Carbapenem Reduction and Decreased Vancomycin-Resistant Enterococcus Infection. (18th September 2019) - Webb, Brandon J; Majers, Jacob; Healy, Regan; Jones, Peter Bjorn; Butler, Allison M; Snow, Greg; Forsyth, Sandra; Lopansri, Bert K; Ford, Clyde D; Hoda, Daanish
Abstract: Background: Antibiotic stewardship is challenging in hematological malignancy patients. Methods: We performed a quasiexperimental implementation study of 2 antimicrobial stewardship interventions in a hematological malignancy unit: monthly antibiotic cycling for febrile neutropenia that included cefepime (± metronidazole) and piperacillin-tazobactam and a clinical prediction rule to guide anti-vancomycin-resistant Enterococcus faecium (VRE) therapy. We used interrupted time-series analysis to compare antibiotic use and logistic regression in order to adjust observed unit-level changes in resistant infections by background community rates. Results: A total of 2434 admissions spanning 3 years pre- and 2 years postimplementation were included. Unadjusted carbapenem and daptomycin use decreased significantly. In interrupted time-series analysis, carbapenem use decreased by −230 days of therapy (DOT)/1000 patient-days (95% confidence interval [CI], −290 to −180; P < .001). Both VRE colonization (odds ratio [OR], 0.64; 95% CI, 0.51 to 0.81; P < .001) and infection (OR, 0.41; 95% CI, 0.2 to 0.9; P = .02) decreased after implementation. This shift may have had a greater effect on daptomycin prescribing (−160 DOT/1000 patient-days; 95% CI, −200 to −120; P < .001) than did the VRE clinical prediction score (−30 DOT/1000 patient-days; 95% CI, −50 to 0; P = .08). Also, 46.2% of Pseudomonas aeruginosa isolates were carbapenem-resistant preimplementation compared with 25.0% postimplementation ( P = .32). Unit-level changes in methicillin-resistant Staphylococcus aureus and extended-spectrum beta lactamase (ESBL) incidence were explained by background community-level trends, while changes in AmpC ESBL and VRE appeared to be independent. The program was not associated with increased mortality. Conclusions: An antibiotic cycling-based strategy for febrile neutropenia effectively reduced carbapenem use, which may have resulted in decreased VRE colonization and infection and perhaps, in turn, decreased daptomycin prescribing. Abstract : Antimicrobial stewardship is challenging in patients with hematological malignancy. After implementation of 2 stewardship initiatives, monthly gram-negative antibiotic cycling and a vancomycin-resistant Enterococcus faecium (VRE) prediction tool, carbapenem use was significantly reduced. This may have resulted in a secondary benefit of reducing VRE colonization and infection and subsequent daptomycin use.